An Arab, an Asian, and a Black Guy Walk into a Job Interview: Ethnic Stigma in Hiring after Controlling for Social Class - Hannah Van Borm; Louis Lippens; Stijn Baert (Institute of Labor Economics (IZA), 2022)
Over the last decades, researchers have found compelling evidence of hiring discrimination toward ethnic minorities based on field experiments using fictitious job applications. Despite increasing efforts to discover why ethnic minorities experience hiring penalties, the academic world has not yet found a satisfying answer. With this study, we aim to close this gap in the literature by conducting a state-of-the-art scenario experiment with genuine American recruiters. In the experiment, we ask recruiters to assess fictitious job applicants of various race-ethnicities but consistent social class. The applicants are rated on 22 statements related to the dominant explanations for ethnic discrimination in hiring that the models of taste-based and statistical discrimination have offered. We find that different race-ethnicity groups are evaluated rather similarly, except for Asian Americans, who are perceived to have better intellectual abilities and organizational skills and to be more ambitious, motivated, efficient, and open. These results suggest that the hiring discrimination found in previous experimental research might be overestimated because part of the reported hiring penalty may be attributed to aspects other than race-ethnicity.
Keywords: J71; J15; J24; 330; hiring; ethnic discrimination; statistical discrimination; social class; stigma